Endothelial dysfunction and cardiovascular diseases in people living with HIV on specific highly active antiretroviral therapy regimen: A systematic review of clinical studies - Haskly Mokoena; Sihle E. Mabhida; Joel Choshi; Phiwayinkosi V. Dludla; Bongani B. Nkambule; Zandile J. Mchiza; Duduzile E. Ndwandwe; André P. Kengne; Sidney Hanser (Atherosclerosis Plus, 2024)
Despite the improved efficacy of highly active antiretroviral therapy (HAART) in viral suppression, emerging evidence indicates an increased burden of noncommunicable diseases in people living with HIV (PLWH). Immune activation and persistently elevated levels of inflammation have been associated with endothelial dysfunction in PLWH, likely contributing to the development of cardiovascular diseases (CVDs). Here, electronic search databases including PubMed, Google Scholar, Cochrane Library, and Science Direct were used to retrieve scientific evidence reporting on any association between markers of endothelial function and CVD-related outcomes in PLWH on HAART. Extracted data was subjected to quality assessment using the Downs and Black checklist. Most (60 %) of the results indicated the presence of endothelial dysfunction in PLWH on HAART, and this was mainly through reduced flow mediated dilation and elevated serum makers of adhesion molecules like ICAM-1, VCAM-1, and P-selectin. The summarized evidence indicates an association between persistently elevated markers of endothelial dysfunction and a pro-inflammatory state in PLWH on HAART. Only a few studies reported on improved endothelial function markers in PLWH on HAART, while limited evidence is available to prove that endothelial dysfunction is associated with CVD-risk, which could be attributed to therapeutic effects of HAART. Limited studies with relatively high quality of evidence were included in this systematic review. In conclusion, results from this review lay an important foundation for future research, even a meta-analysis, that will improve the understanding of the contributing factors to the burden of CVDs in PLWH on HAART.